Identification and distinction of two Paragonimus metacercaria types found in the same crab species Potamiscus tannanti Rathbun, 1904 collected in Yenbai province - Le, Nguyen Thi; Doanh, Pham Ngoc; Minh, Nguyen Thi; Ha, Nguyen Van (Academia Journal of Biology, 2014)
Although three species of the genus Paragonimus Braun, 1899, including P. westermani (Kerbert, 1878), P. heterotremus Chen et Hsia, 1964 and P. ohirai Miyazaki, 1939, have been recorded in Vietnam, only the metacercaria of P. heterotremus has been collected by previous authors. During investigations in the Yenbai province, we have collected two types of Paragonimus metacercariae in the same freshwater crab, Potamiscus tannanti (Rathbun, 1904). They remarkably differed from each other in morphology and size. The small metacercariae which were 0.212 ± 0.018 ´ 0.187 ± 0.016 mm in size, had thick inner cyst wall. In contrast, the bigger metacercariae, which were found for the first time in Vietnam, were 0.811 ± 0.079 ´ 0.775 ± 0.100 mm in size and provided with thin inner cyst wall, occupying the entire space of the cyst. The small metacercariae types and its adult worms were completely identical to P. heterotremus. In contrast, the big metacercaria types and its adult worms recovered from experimental dogs and cats differed from other known Paragonimus species. Morphologically, they were somewhat similar to P. skrjabini Chen, 1959 and P. harinasutai Miyazaki and Vajrasthira, 1967, but different from them either in metacercaria stage or adult worm. These Paragonimus sp. samples collected from the Yenbai province of Vietnam, might be of a new species to science.